2D Modelling of the Breakdown Voltage of Hybrid Dielectric (Gas and Solid) System - Muzamil, Sanupal; Wisnujati, Andika (Universitas Sarjanawiyata Tamansiswa, 2025)
Sulfur hexafluoride (SF6) has been used over decades due to its excellent dielectric, arc quenching and heat transfer properties, but has tremendous global warming potential. It is therefore mandatory to find more environmentally friendly alternatives by designing of future eco-friendly hybrid insulation (solid and gas) system that require a thorough understanding of the evolution of electric field in such structure. A numerical model was developed using finite element method (FEM) of a commercial software Comsol® Multiphysics. Using electrostatic equations, the 2D model stability, 2D boundary model and voltages are varied in order to identify their influence on the electric field distribution. Numerical simulations show that maximum electric fields will vary significantly according to distances of point-dielectric (gap). The maximum electric field increases if the gap (electrode tip-planar) size is shorter. Additionally, the electric field is not linearly spread in solid dielectric material and more concentrated around the edges of solid dielectric.